Effect Of Lavender Oil Aromaterapy On Menstrual Pain In Students AT SMPN18 PESAWARAN In 2020 - Sabrima, Eby Juliana; Riona Sanjaya; Surmiasih; Yona Desni Sagita (Biomedical Journal of Indonesia, 2020)
The problem of primary dysmenorrhoea is largely overcome by resting and takingmedication. Many ways to eliminate or reduce dysmenorrhea both pharmacologicallyand non-pharmacologically. Management of menstrual pain can also be managed non-pharmacologically, such as giving aromatherapy, aromatherapy administrationtechniques can use a variety of aromatherapy such as lavender. The purpose of thisstudy was to determine the effect of Lavender Oil Aromatherapy on Menstrual Pain inStudents at SMP N 18 Pesawaran in 2020. This type of quantitative research design isquasy experimental design research with one grub pretest and posttest approach. Thepopulation in this study were all students. Samples taken in this study were 31students who experienced disminore when the study took place. Analysis of the dataused using the Wilcoxon test. The results of data analysis and processing found thatthere was an effect of Lavender Oil Aromatherapy on Menstrual Pain in Junior HighSchool 18 Pesawaran in 2020 with a p-value of 0,000 <0.05. Respondents can increasetheir knowledge about handling disminorea by searching for information via theinternet or reading books, so that respondents are not dependent on pharmacologicaltreatment alone.